Finite Element Simulation on Damage and Fracture Properties of a Ring Cut from Filament-Wound Pipes with and without Delamination - Ahmad Zaidi, A.M.; Abdul Hamid, H.; Ghazali, M.I.; Abdul Rahman, I.; Mahzan, S.; Yusof, M.S. (International Journal of Integrated Engineering, 2009)
The technological advances in various industries have increased the demands on new engineered material tremendously since conventional materials such as steel, failed to perform in severe conditions. Nowadays, composite materials especially fibre-reinforced plastic composites (FRP) are broadly being used in many engineering fields to manufacture critical components with high stress concentration, exposure to extreme surrounding or weight constraint. However, they often suffer from a characteristic weakness, i.e. they are prone to interlaminar damage, often in a form delamination. In order to assess the development and the consequences of such damage, interlaminar fracture properties are essential. In this study, the ring cut specimen from filament-wound pipes with and without delamination was modelled and simulated based on experimental work using finite element modelling to further assist the identification and determination of the fracture properties. Investigation also involves the effect of the delamination length to the Energy Release Rate, G. Comparison between 23mm delamination of simulation and experimental results from [7] is presented.